The logistic management of construction sites - Maslinda, Daud (2010)
Logistic is defined as the moving materials and equipment to where the they will be used.In construction,the efficient management of logistic give impact of the quality in construction.Therefore,in managing the logistic its depend on the activities schedule and suppliers.The delivery of all materials and equipment on site should be arrived at the right time and placed at the right location.The effectiveness of logistic flow and delivery process of materials to the construction is important to make the construction are smoothly construct without facing any problems occur.The area of this case study is in Kuantan and Segamat area which is the medium contractor (class C) are choosed.The data collection is to investigate the information of logistic management on site.All parties involves in the logistic construction and they are responsible to make the management is efficient.Project manager is the top level in managing the materials at site. Therefore,the good communication and cooperation among the parties involved can help the project manager to handle the logistic on site in getting the information of materials needed.The delivery materials to the site based on the schedule,suppliers and activities construction of the project to prevent the materials stock-out and problem in construction activities.Thus,all parties are responsible in managing the logistic flow in giving the information correctly and proper coordination is needed in delivery materials to the site.